OMNIBUS LAW DAN KRISIS LEGAL DRAFTING: EVALUASI KEGAGALAN UU CIPTA KERJA DAN REKOMENDASI REFORMASI LEGISLASI - Parningotan Malau; Natashya Simaremare; Owen Doly Ambarita; Johannes Bonatua Marpaung; Edward Muliandino; Andika Simamora (Journal of Innovation Research and Knowledge, 2025)
The omnibus law approach in Indonesia was introduced as a solution to overlapping and conflicting regulations. However, its application in the Job Creation Law has generated significant issues, particularly in the area of legal drafting. This article critically examines the drafting failures of the law based on the principles of proper regulatory formation as outlined in Law No. 12 of 2011 in conjunction with Law No. 13 of 2022. Through case analysis, theoretical perspectives, and comparative reviews of international practices in the United States, Canada, and the Philippines, the article argues that the core problem of the omnibus law lies not in its concept, but in its poor drafting structure, legal ambiguity, excessive delegation of authority, and lack of public participation. The article concludes by offering five key recommendations to reform Indonesia’s legal drafting process so that the omnibus law can serve as a legitimate, effective, and democratic instrument of regulatory harmonization